Features of franchising in Ukraine - Kravtsova, Julia (My University, 2014)
In the study substance of such form of conducting of the business as franchising have been considered. The common features of the use of franchising in Ukraine have been analyzed. Also an analytical review of development of franchising in 2011-2013 have been pointed and identified preconditions of growth of the franchising market have been showed, and the problems of franchising development in Ukraine have been analyzed.Stability in the economy and a developed market for small and medium businesses. For the appearance of progressive ideas business requires In Ukraine, SMEs are under development. In addition, given the state of crisis, it is very risky to start a business from scratch. More reliable is to use ready-made projects, ie those that offer franchisors. Franchise serves as a corporate strategy of small and medium enterprises. It is therefore necessary to reflect the main characteristics, problems of franchising, the efficiency of its use in Ukraine in order to show all perspectives.
Keywords: franchising; development; business; франчайзинг; розвиток; бізнес; бизнес; развитие